Moderation and coexistence with psychoactive substances use: Approaching a Drug Consumption Room in France - Mendonça, Natália Heringer (Anuário Antropológico, 2023)
This article aims to understand how it is for psychoactive users to experience the use of substances in a Drug Consumption Room (DCR) for harm reduction and how it impacts their lives and subjectivities. The work starts from the premise that the DCRs’ polemical implementation is an attempt to answer to the social process that turned the use of psychoactive substances into a crime/health issue and created the pathological, excluded, and punishable category of drug user/addict. A qualitative methodology was used blending interviews and a direct observation of the Strasbourg’s DCR (ARGOS). The results show that psychoactive users attending that structure are persistently concerned about hygiene, responsibility, and guilt, which signalizes a searching for adhering to social order intercalated with substance use, however, still transversed by controversial feelings related to their consumption. Also expressing their autonomy, they reformulate the meanings they give to their substance consumption and to themselves. In addition, Strasbourg’s DCR’s sensibility to its audience’s precariousness gives clues for reflecting on this facility as an agent who acts by conviction in the face of the tragedy this population lives in.